2022
DOI: 10.1111/aec.13250
|View full text |Cite
|
Sign up to set email alerts
|

Mosquito (Diptera: Culicidae) diversity along a rainy season and edge effects in a riparian forest in Southeastern Brazil

Abstract: Knowledge on the distribution of mosquito communities over time and across human‐modified landscapes is important in determining the risk for vector‐borne disease. The diversity of mosquitoes along a rainy season and edge effects were evaluated in a riparian forest in the Cerrado biome, Southeastern Brazil. Mosquito communities were sampled with Shannon traps in three distinct habitats (forest interior, forest edge and pasture) throughout an entire rainy season, comprising five sampling months (December 2015 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 66 publications
0
4
0
Order By: Relevance
“…We also found that species evenness was slightly, but significantly lower during the rainy season compared to the dry season. While higher diversity is generally associated with rainy months 11 , our findings may reflect an increased dominance of Hg. janthinomys , Ps.…”
Section: Discussionmentioning
confidence: 51%
See 2 more Smart Citations
“…We also found that species evenness was slightly, but significantly lower during the rainy season compared to the dry season. While higher diversity is generally associated with rainy months 11 , our findings may reflect an increased dominance of Hg. janthinomys , Ps.…”
Section: Discussionmentioning
confidence: 51%
“…Rural edges also appear to enhance permeability for sylvatic vectors 8 and inevitably their pathogens. Studies failing to detect higher diversity at forest edges have often restricted sampling to within a few hundred meters of the boundary [9][10][11]59 , yet we have only detected substantially lower diversity when sampling beyond 500 m into the forest 17,18 . We also found that species evenness was slightly, but significantly lower during the rainy season compared to the dry season.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Although culicid species respond differently to deforestation, disease‐vector mosquitoes usually are positively affected by anthropogenic impacts (Burkett‐Cadena and Vittor 2018). The high abundance of mosquitoes in the early succession areas can be attributed to floodwater species such as Aedes scapularis and Psorophora (Ferreira et al 2016), which dramatically proliferate during the rainy season (Costa et al 2023). These species breed in ponds on the ground and prefer open vegetation areas where the increased amount of sunlight stimulates algae growth, and herbaceous plants provide nectar for adult mosquitoes.…”
Section: Discussionmentioning
confidence: 99%